PENGARUH ETIKA PROFESI, PENGALAMAN, PENGETAHUAN DAN GENDER TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS (Studi Empiris pada KAP Padang Dan Pekanbaru) - Anggara, M. Agung; Anugerah, Rita; Alamsyah, Mudrika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to analyze how professional ethic, experience, knowledge and gender affect to the materiality judgement by empirical at KAP Padang and Pekanbaru as the object of research. This research was held on September 12th until the end of September 2016. The method of analysis used in this study is multiple linear regression analysis. Determination of the sample using purposive sampling method and obtained samples is 74 auditors consist of 48 female auditors and 26 male auditors. The results of this study showed that professional ethic have influence on materiality judgement with significant values 0.004. Experience have influence on materiality judgement with significant values 0.007. Knowledge have influence on materiality judgement with significant values 0.015. Gender didn’t have influence on Materiality judgement with significant values 0.553, it explained by equity model theory that male and female as a professional is identic, so need the same way to manage them. Based on total Adjusted R-Square result, proved that professional ethic, experience, knowledge, and gender effect to materiality judgement in amount of 62% while the rest of 38% were affect by other variables that were not performed in this study. So, for the next research adding more variables are suggested.Keywords : ethic, experience, knowledge, gender, and materialty